2019
DOI: 10.1186/s40644-019-0191-y
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of high nodal burden with ultrasound and magnetic resonance imaging in clinically node-negative breast cancer patients

Abstract: BackgroundAlthough the role of axillary imaging has been redirected for predicting high nodal burden rather than predicting nodal metastases since ACOSOG Z1011 trial, it remains unclear whether and how axillary lymph node (ALN) characteristics predicts high nodal burden. Our study was aimed to evaluate the predictive value of imaging characteristics of ALNs at ultrasound and magnetic resonance imaging (MRI) for prediction of high nodal burden (≥3 metastatic ALNs) in clinically node-negative breast cancer patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 26 publications
(23 reference statements)
1
20
0
Order By: Relevance
“…Further, the presence of extensive nodal involvement is significantly associated with the number of sonographically suspicious nodes in these studies [12, 17, 18, 21, 2531]. For instance, Kim et al [18] showed that the percentage of patients with ≥3 positive nodes was 3.1% vs. 38.5% vs. 62.5% in case of ≤1, 2, or ≥3 sonographically suspicious nodes ( P < 0.001). In multivariate analysis, the odds ratios for ≥3 positive nodes were significantly increased when two suspicious nodes were seen (OR 6.52, 95% CI 1.36–31.28) and when more than two suspicious nodes were seen (OR 21.08, 95% CI 2.57–172.86) [18].…”
Section: Resultsmentioning
confidence: 88%
See 4 more Smart Citations
“…Further, the presence of extensive nodal involvement is significantly associated with the number of sonographically suspicious nodes in these studies [12, 17, 18, 21, 2531]. For instance, Kim et al [18] showed that the percentage of patients with ≥3 positive nodes was 3.1% vs. 38.5% vs. 62.5% in case of ≤1, 2, or ≥3 sonographically suspicious nodes ( P < 0.001). In multivariate analysis, the odds ratios for ≥3 positive nodes were significantly increased when two suspicious nodes were seen (OR 6.52, 95% CI 1.36–31.28) and when more than two suspicious nodes were seen (OR 21.08, 95% CI 2.57–172.86) [18].…”
Section: Resultsmentioning
confidence: 88%
“…These studies concluded that the mean number of positive axillary nodes is significantly higher amongst patients with their positive nodes identified by AxUS than by SNB [14, 19, 24]. Further, the presence of extensive nodal involvement is significantly associated with the number of sonographically suspicious nodes in these studies [12, 17, 18, 21, 2531]. For instance, Kim et al [18] showed that the percentage of patients with ≥3 positive nodes was 3.1% vs. 38.5% vs. 62.5% in case of ≤1, 2, or ≥3 sonographically suspicious nodes ( P < 0.001).…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations